Effects of alpha lipoic acid on loss of myelin sheath of sciatic nerve in experimentally induced diabetic rats - Demir, C. F.; Tasci, I.; Kuloglu, T. (Wiley, 2018)
[Abstract Not Available]
4th Congress of the European-Academy-of-Neurology (EAN) -- JUN 16-19, 2018 -- Lisbon, PORTUGAL